Psychosocial Implications of COVID-19 on Head and Neck Cancer - Sarah M. Dermody; Andrew G. Shuman (Current Oncology, 2022)
The COVID-19 pandemic has fundamentally changed healthcare access, delivery, and treatment paradigms throughout oncology. Patients with head and neck cancer comprise an especially vulnerable population due to the nature of their disease and the transmission mechanism of the SARS-CoV-2 virus. The consequences of triage decisions and delays in care have serious psychosocial implications for patients. The development of structured psychosocial support programs, coupled with clear and consistent communication from treating physicians, can help mitigate perceptions of abandonment and distress that may accompany delays in care. As the unpredictability of the pandemic’s course continues to burden both providers and patients, we must be proactive in addressing the psychosocial implications of these delays in care.